Effects of cotton genotype, defoliation timing and season on fiber cross-sectional properties and yarn performance. Issue 17 (September 2021) - Long, Robert L; Delhom, Christopher D; Bange, Michael P
Cotton fiber cross-sectional properties influence the performance of ring spun yarns. The spinning performance of two Gossypium hirsutum L. Upland cotton genotypes known to have inherently different fiber fineness properties were compared. Genotypes were grown together in field experiments conducted over two growing seasons, and crops were subjected to early and late defoliation treatments. The aim was to quantify the differences in yarn properties following changes targeting fiber fineness properties in isolation from other fiber properties. For the first time, the percentage difference in yarn properties was captured along with the associated changes made to alternative fiber fineness properties within the base micronaire 3.50 to 4.90 G5 range. As expected the genotype with lower fiber micronaire, linear density, and perimeter, spun yarns that were stronger and more even. Late defoliated cotton plants produced fibers that were higher in micronaire and maturity ratio, and were bigger in perimeter, which demonstrated that the fibers had expanded during the secondary wall thickening phase of development. However, the defoliation treatment effect on fiber fineness properties was smaller compared with the effect of genotype, and no change to any yarn property was detected. In terms of environmental effects, the first season cotton had smaller perimeter finer fibers that spun stronger and more even yarns. In contrast, the second season cotton had bigger perimeter fibers that spun weaker and less even yarns.